The Statistical Relationship between Economic Growth and Total Energy Use: Evidence from Panel Co-integration and Granger-causality Investigation of SSA Countries - Sekanabo, Desire; Nyandwi, Elias; Dieu, Hakizimana Khan Jean de; Thomas, Valerie M. (International Journal of Energy Economics and Policy, 2022)
This study analyses the statistical relationship between economic growth and total energy use in Sub Saharan Africa (SAA) member countries in the period between 1989 and 2017. The panel unit root test, panel co-integration test, vector error correction and vector auto regressive Granger Causality/Block Exogeneity Wald Tests are employed. The results are that economic growth in SAA is linked to total energy and total energy is linked to economic growth. The growth in available energy forecasts economic growth which, in turn, forecasts the use of energy in SAA. The bidirectional relationship is further explored for SSA sample countries. The results suggest that economic growth in SSA can be supported by promoting growth in productivity of the energy industries.